Superior low cycle fatigue property from cell structures in additively manufactured 316L stainless steel. (1st June 2022) - Cui, Luqing; Deng, Dunyong; Jiang, Fuqing; Peng, Ru Lin; Xin, Tongzheng; Mousavian, Reza Taherzadeh; Yang, Zhiqing; Moverare, Johan
Abstract: We have investigated the low cycle fatigue (LCF) properties and the extent of strengthening in a dense additively manufactured stainless steel containing different volume fractions of cell structures but having all other microstructure characteristics the same. The samples were produced by laser powder bed fusion (L-PBF), and the concentration of cell structures was varied systematically by varying the annealing treatments. Load-controlled fatigue experiments performed on samples with a high fraction of cell structures reveal an up to 23 times increase in fatigue life compared to an essentially cell-free sample of the same grain configuration. Multiscale electron microscopy characterizations reveal that the cell structures serve as the soft barriers to the dislocation propagation and the partials are the main carrier for cyclic loading. The cell structures, stabilized by the segregated atoms and misorientation between the adjacent cells, are retained during the entire plastic deformation, hence, can continuously interact with dislocations, promote the formation of nanotwins, and provide massive 3D network obstacles to the dislocation motion. The compositional micro-segregation caused by the cellular solidification features serves as another non-negligible strengthening mechanism to dislocation motion. Specifically, the cell structures with a high density of dislocation debris also appear to act as dislocation nucleation sites, very much like coherent twin boundaries. This work indicates the potential of additive manufacturing to design energy absorbent alloys with high performance by tailoring the microstructure through the printing process.